Detection of time of birth and cord clamping using thermal video in the delivery room - Kolstad, Vilde; García-Torres, Jorge; Brunner, Sara; Johannessen, Anders; Foglia, Elizabeth; Ersdal, Hege; Meinich-Bache, Øyvind; Rettedal, Siren (Frontiers in Pediatrics, 2024)
Introduction: Newborn resuscitation algorithms emphasize that resuscitation is time-critical, and all algorithm steps are related to the time of birth. Infrared thermal video has the potential to capture events in the delivery room, such as birth, cord clamping, and resuscitative interventions while upholding the privacy of patients and healthcare providers.Objectives: To i) investigate the technical feasibility of using thermal video in the delivery room to detect birth and cord clamping, and ii) evaluate the accuracy of manual real-time registrations of time of birth and cord clamping by comparing it to registrations abstracted from thermal videos.